Clinical and psychosocioeconomic impact of COVID-19 pandemic on patients of the Indian Progressive Systemic Sclerosis Registry (IPSSR). Issue 2 (23rd April 2021) - Kavadichanda, Chengappa; Shobha, Vineeta; Ghosh, Parasar; Wakhlu, Anupam; Bairwa, Devender; Mohanan, Manju; Janardana, Ramya; Sircar, Geetabali; Sahoo, Rasmi Ranjan; Joseph, Sneha; Negi, Vir Singh; Khanna, Dinesh; et al.
Abstract: Objectives: The aim was to determine the impact of the coronavirus disease 2019 (COVID-19) pandemic on access to health care among patients with scleroderma and to analyse the economic and psychosocial impacts and the infection prevention measures taken by them during the pandemic. Methods: A 25-item questionnaire designed to assess the components of the objectives was tele-administered between October 2020 and January 2021 to the patients enrolled in the Indian Progressive Systemic Sclerosis Registry. Results: Of the 428 patients in the registry, 336 took part in the study. A scheduled outpatient visit was missed by 310 (92.3%) patients, and 75 (22.3%) skipped prescription drugs. During the pandemic, 75 (22.3%) had a family member lose a job. Financial difficulties were reported by 155 (46.1%), with 116 (34.5%) patients having to spend an additional INR 4000 (2000–10 000) [USD 54.9 (27.0–137.4)] to continue treatment. Although 35 patients (10.4%) had at least one symptom suggestive of COVID-19, infection was confirmed in only 4. None of them needed hospitalization or had adverse outcomes. Worsening of scleroderma was seen in 133 (39.6%) individuals, with 15 (4.5%) requiring hospitalization. Most (96%) of the patients were aware of infection prevention measures, and 91 (27.1%) had taken unproven prophylactic medications. Conclusion: Individuals with scleroderma in India have been affected during the pandemic owing to closure of hospital services, lack of transport, loss of jobs and the additional financial burden. Health-care providers should continue to educate patients to stay on their medications and encourage them to be vaccinated for COVID-19.